2007
DOI: 10.1159/000104148
|View full text |Cite
|
Sign up to set email alerts
|

The Transdifferentiation of Bone-Marrow-Derived Cells in Colonic Mucosal Regeneration after Dextran-Sulfate-Sodium-Induced Colitis in Mice

Abstract: Bone-marrow-derived cells (BMDCs) transdifferentiate into various types of gastrointestinal cells. The precise transdifferentiation of BMDCs in gut regeneration, however, is controversial. In this study, we examined the transdifferentiation of BMDCs in the regeneration of damaged colonic epithelia. Lethally irradiated wild-type female mice (C57BL/6) were rescued by bone marrow transplantation from male green fluorescent protein transgenic mouse donors. Chronic colitis was induced by administering 3% dextran su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 50 publications
2
24
0
Order By: Relevance
“…Both in animal models as well as in patients, it seems that BMCs are involved in the healing process after intestinal injury. 20,[31][32][33][34] In our work, we detected BM-transplanted cells in the intestine, suggesting that another effect, rather than immunosuppression, may also contribute to regeneration or modulation of the local inflammatory response, as cytokine interplay was somewhat different between both treated groups. In accordance, biopsy specimens from the gastrointestinal tract of women who had received male BM transplants presented donor-derived epithelial cells in every part of the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 59%
“…Both in animal models as well as in patients, it seems that BMCs are involved in the healing process after intestinal injury. 20,[31][32][33][34] In our work, we detected BM-transplanted cells in the intestine, suggesting that another effect, rather than immunosuppression, may also contribute to regeneration or modulation of the local inflammatory response, as cytokine interplay was somewhat different between both treated groups. In accordance, biopsy specimens from the gastrointestinal tract of women who had received male BM transplants presented donor-derived epithelial cells in every part of the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 59%
“…TGFβ1 receptor signaling has been shown to play an essential role during the pathogenesis and recovery of inflammation-related colitis [3,4,5,6,7], but through unclear mechanism. Also, MSCs transplantation has been reported to promote the recovery from DSS-induced colitis [9,10,11,12], whereas the underlying molecular mechanisms remain largely undefined.…”
Section: Discussionmentioning
confidence: 99%
“…However, the precise mechanisms have not been completely clarified. Recently, transplantation of bone-marrow derived cells, or particularly mesenchymal stem cells (MSCs), has been found to reduce the severity of, and improve the recovery from DSS-induced colitis [9,10,11,12]. Moreover, modulated TGFβ receptor signaling by MSCs in the injured colon has been indicated as a cause for the effect of MSCs [12], whereas the exact sources for TGFβ receptor ligands are not defined, and a direct causal link has not been proved.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown that bone marrow-derived cells contribute to the healing of gastrointestinal wounds in humans (Okamoto et al, 2002;Matsumoto et al, 2005) and animals (Brittan et al, 2002(Brittan et al, , 2005Komori et al, 2005a,b;Bamba et al, 2006;Hayashi et al, 2007;Khalil et al, 2007). Moreover, bone marrow-derived cells are recruited more efficiently to the injured gut than to a healthy gut, suggesting a rescue response for assisting with the recovery from damage (Komori et al, 2005a,b).…”
mentioning
confidence: 99%